Development and application of a live transmitting player-mounted head camera - Croft, H.; Suwarganda, E. K.; Syed O.; Syed F. (Sports Technology, 2013)
The use of player-mounted cameras (PMCs) in sport is not new; however, most existing PMC devices do not have the ability to transmit footage as it is captured. This appears to be due to the size and cost of transmitters, batteries and aerials. Instead, the footage is normally stored locally (within the device) on a hard drive or a removable secure digital card. Due to this limitation, PMC devices are not often utilized for coaching feedback, as there is significant delay before being able to view the footage. This paper will describe the development of a novel, non-intrusive PMC that transmits player vantage point footage in real time, captured to a viewing laptop for immediate review by coaches and players. Applications of this technology to rugby union, karate and silat (a South-East Asian martial art) will be described, outlining how the coaches utilize the technology to demonstrate important visual cues to players for the improvement of decision-making. Finally, the strengths and limitation of this technology will be discussed with recommendations for future development.